2016
DOI: 10.1094/cchem-04-16-0120-r
|View full text |Cite
|
Sign up to set email alerts
|

Moisture Effects on the Prediction Performance of a Single‐Kernel Near‐Infrared Deoxynivalenol Calibration

Abstract: Fusarium head blight (FHB) is a serious disease in wheat that affects grain quality owing to the accumulation of mycotoxins such as deoxynivalenol (DON) in grains. Near‐infrared (NIR) spectroscopy has been used to develop techniques to estimate DON levels in single wheat kernels to facilitate rapid, nondestructive screening of FHB resistance in wheat breeding lines. The effect of moisture content (MC) variation on the accuracy of single‐kernel DON prediction by NIR spectroscopy was investigated. Sample MC cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 48 publications
0
9
0
Order By: Relevance
“…However, studies on the moisture effects on the performance of NIR spectroscopy calibrations for cereal grain traits analysis are limited. Peiris, Dong, Bockus, and Dowell (2016) showed that grain moisture content influences the NIR spectroscopy prediction of deoxynivalenol levels in wheat grains. Since water is a strong NIR absorber (Büning-Pfaue, 2003), moisture level variability in grains may significantly influence the spectral features.…”
mentioning
confidence: 99%
“…However, studies on the moisture effects on the performance of NIR spectroscopy calibrations for cereal grain traits analysis are limited. Peiris, Dong, Bockus, and Dowell (2016) showed that grain moisture content influences the NIR spectroscopy prediction of deoxynivalenol levels in wheat grains. Since water is a strong NIR absorber (Büning-Pfaue, 2003), moisture level variability in grains may significantly influence the spectral features.…”
mentioning
confidence: 99%
“…Furthermore, NIR spectroscopy can be used as an online analysis tool capable of testing a large amount of sample during processing. Finally, various factors other than the quality parameters of the sample, for example, sample shape, moisture, particle size, color, texture, and density, affect the NIR spectra, which may add some complications to the interpretation of the NIR data (Peiris, Dong, Bockus, & Dowell, 2016;Weir, Omielan, Lee, & Rajcan, 2005;Williams, 2007). NIR spectroscopy is also a nondestructive, safe, environmentally clean (no chemicals), and easy-to-use technique which requires simple or no sample preparation.…”
Section: Near-infrared (Nir) Spectroscopymentioning
confidence: 99%
“…NIR spectroscopy can be calibrated and validated against highly accurate techniques, with the flexibility to analyze more than 30 characteristic factors of cereals and pulses in a single test (Williams, 2007). For example, NIR calibration for deoxynivalenol (DON) levels in wheat kernel was shown to be significantly affected by moisture content (MC) leading to over-and underestimation of DON levels at decreased and increased MC, respectively (Peiris et al, 2016). On the other hand, there is always a need to calibrate the NIR instrument for each type of cereal and for varying environments as this method requires a large database in order for the data to be considered reliable (Akkaya et al, 2016).…”
Section: Near-infrared (Nir) Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…The moisture content of grain samples affects the accuracy of DON estimation by NIR spectroscopy; the estimated DON levels are over-and underestimated at lower and higher equilibrium moisture contents, respectively (Peiris et al 2016). Additionally, grain samples may differ in moisture level at the time of analysis.…”
mentioning
confidence: 99%